Fiber-coupled fluorescence light source suitable for spectroscopic applications - Vladev, Veselin P; Eftimov, Tinko A; Bozhkov, Stefan I; Nikolova, Krastena T; Minkova, Stefka P; Blazheva, Denitsa E; Angelova, Galena V; Brazkova, Maria S (Photonics Letters of Poland, 2022)
An experimental study of a fluorescent broadband light source fully compatible with optical fibers is presented in the article, with the aim of using it for excitation-emission matrix fluorescence spectroscopy. A fiber optic glass ferrule filled with a solution of Rhodamine 6G in glycerin was used for the basic construction of the light source. The ferrule is coupled with optical fibers to illuminate the dye medium and to receive the fluorescent signal. A tuning of the light spectrum from the source between 528 nm and 660 nm with a shift of 1 nm is achieved by means of a monochromator. Full Text: PDF References N. Hoinka and T. Fuhrmann-Lieker, "Amplified Spontaneous Emission in Paper", Sci. Rep. 9, 1 (2019), CrossRef J. Włodarski, M. Chychłowski, "Chemically tuned light source with an optical pump", Photonics Lett. Pol. 13(2), 46 (2021). CrossRef J. Żmojda, P. Miluski, M. Kochanowicz, J. Dorosz, A. Baranowska, M. Leśniak and D. Dorosz, "Luminescent properties of active optical fibers", Photonics Lett. Pol. 11(2), 50 (2019). CrossRef K. Jakubowski, W. Kerkemeyer, E. Perret, M. Heuberger, R. Hufenus, "Liquid-core polymer optical fibers for luminescent waveguide applications", Mater. Des. 196, 1 (2020). CrossRef V. Vladev, T. Eftimov, "Fiberized fluorescent dye microtubes", Proc. SPIE 8770, 87700V-1 (2013). CrossRef V. Vladev, T. Eftimov, W. Bock, "Broad-band fluorescent all-fiber source based on microstructured optical fibers", Photonics Lett. Pol., 7(2), 41 (2015). CrossRef V. Vladev, T. Eftimov, W. Bock, "Fluorescent all-fiber light source based on micro-capillaries and on microstructured optical fibers terminated with a microbulb", Opt. Comm. 356, 34 (2015). CrossRef V. Vladev, T. Eftimov, S. Nedev, "Excitation efficiency of a side-pumped fiberized fluorescent dye microcapillary", Opt. Fib. Tech. 28, 28 (2016). CrossRef V. Vladev, M. Todorova, V. Slavchev, M. Brazkova, E. Belina, S. Bozhkov, P. Radusheva, "A new basic structure suitable for a fully integrated all-fiber-optic stimulated emission dye source", J. Phys.: Conf. Ser. 1859 (012059), 1 (2021). CrossRef V. P. Vladev, M. M. Todorova, M. S. Brazkova, S. I. Bozhkov, "Diode-pumped all-fiber-optic liquid dye laser", Laser Phys. Lett. 18 (11), 115103 (2021), CrossRef G. Dyankov, T. A. Eftimov, N. Malinowski, E. Belina, H. Kisov, P. Mikulic, W. J. Bock, "A highly efficient biosensor based on MAPLE deposited hemoglobin on LPGs around phase matching turning point", Opt. Laser Technol. 123, 1 (2020). CrossRef T. Eftimov, G. Dyankov, A. Arapova, P. Kolev and V. Vladev, W4.73 , OFS-27, Optical Fiber Sensor Conference - 2022, 29 Aug- 2 Sept., The Westin Alexandria, Alexandria, Virginia, USA. CrossRef G. Rossi, J. Durek, S. Ojha, O. K. Schlüter, "Fluorescence-based characterisation of selected edible insect species: Excitation emission matrix (EEM) and parallel factor (PARAFAC) analysis", CRFS 4, 862 (2021). CrossRef L. Li, Y. Wang, W. Zhang, S. Yu, X. Wang, N. Gao, "New advances in fluorescence excitation-emission matrix spectroscopy for the characterization of dissolved organic matter in drinking water treatment: A review Author links open overlay panel", Chem. Eng. J. 381, 1 (2020). CrossRef